Maritime Shipping and Export Trade on “Maritime Silk Road” - Bao Jiang; Jian Li; Chunxia Gong (Asian Journal of Shipping and Logistics, 2018)
The initiative of the 21st-Century Maritime Silk Road will not only enhance China's international trade with countries along the road, but will also bring opportunities and challenges to China's maritime shipping industry. This article examines correlations between freight rate and the export trade on the five shipping routes of the Maritime Silk Road by the VAR model. The empirical results show that among the five routes, on the Persian Gulf route and European route, export has a significantly negative impact on freight index; however, on the Southeast Asian route and Taiwanese route freight index has a significantly negative effect on exports. Finally, some strategies were put forward on the Chinese shipping market and industry. Keywords: The 21st-Century Maritime Silk Road, SCFI, Export Trade, VAR Model